Loudspeaker FEM modelling: Characterisation of critical aspects in acoustic impedance measure through electrical impedance. (September 2017) - Bianco, Francesco; Teti, Luca; Licitra, Gaetano; Cerchiai, Mauro
Abstract: A loudspeaker can be seen as a device coupling different acoustic, mechanic and electric systems by a series of impedance adaptations. A simple model can thus allow the determination of the acoustic impedance seen by the speaker membrane from measuring the electric impedance of the device. Given a certain number of assumption on mechanical modes and on the strictly electric components, this approach in principle is valid through a wide frequency range. Applying this method with a loudspeaker or a similar device allows to perform acoustic impedance measurements, as shown by Ahadi and Bakhtiar in a previous work. Unfortunately, when trying to apply straightforwardly this method, many difficulties arise. In this paper, using a FEM simulation of a loudspeaker in specific mounting conditions, critical aspects are highlighted to improve the range of application of the measurement technique. Moreover, the role of the speaker' s geometry is separately analysed and possible methods to overcome the limitations of the measuring method are provided. Further developments will be necessary to deal with time varying and nonlinear properties of the speaker.